Targeted therapy approaches for epithelial-mesenchymal transition in triple negative breast cancer - Haque, Mazharul; Shyanti, Ritis K.; Mishra, Manoj K. (Frontiers in Oncology, 2024)
Triple-negative breast cancer (TNBC) is distinguished by negative expression of estrogen receptor (ER), progesterone receptor (PR), and human epidermal growth factor receptor 2 (HER2), making it an aggressive subtype of breast cancer and contributes to 15-20% of the total incidence. TNBC is a diverse disease with various genetic variations and molecular subtypes. The tumor microenvironment involves multiple cells, including immune cells, fibroblast cells, extracellular matrix (ECM), and blood vessels that constantly interact with tumor cells and influence each other. The ECM undergoes significant structural changes, leading to induced cell proliferation, migration, adhesion, invasion, and epithelial-to-mesenchymal transition (EMT). The involvement of EMT in the occurrence and development of tumors through invasion and metastasis in TNBC has been a matter of concern. Therefore, EMT markers could be prognostic predictors and potential therapeutic targets in TNBC. Chemotherapy has been one of the primary options for treating patients with TNBC, but its efficacy against TNBC is still limited. Targeted therapy is a critical emerging option with enhanced efficacy and less adverse effects on patients. Various targeted therapy approaches have been developed based on the specific molecules and the signaling pathways involved in TNBC. These include inhibitors of signaling pathways such as TGF-β, Wnt/β-catenin, Notch, TNF-α/NF-κB and EGFR, as well as immune checkpoint inhibitors, such as pembrolizumab, 2laparib, and talazoparib have been widely explored. This article reviews recent developments in EMT in TNBC invasion and metastasis and potential targeted therapy strategies.